In the context of signal processing, consider the following system: $$ x\left( t \right) \to System\, A \to z\left( t \right) \to System \, B \to y\left( t \right) .$$
Let the global system be the "union" of system A and system B. The input and output of System A are represented by the equations:
$$ \frac{d^2 \, z(t)}{d \, t^2} + 6 \frac{d\, z(t)}{d\, t} + 8 z\left( t \right) = \frac{d\, x(t)}{d\, t} + 2x\left( t \right) $$
and the unit impulse response of System B is defined as follows: $$ h_B \left( t \right) = t e^{-3t} u\left( t \right) .$$
Q1: What is the unit impulse response of the global system?
Q2: For a periodic input of the form
$$
x\left( t \right) =e^{-t} \quad ; \quad -1<t<0
.$$
with a period of $T=1$, what will the output signal $y\left( t \right) $ be?
Q3: What is the frequency spectrum of that last signal?
Note: In this problem $u(t)$ denotes the unit step function. And I found these three articles that I think are related.
Edit: With the help of @KwinvanderVeen , I tried to solve it by finding the transfer function for both systems. $$ H_A(s)= \frac{Z\left( s \right) }{X\left( s \right) } = \frac{\mathcal{L}\{z\} \left( s \right) }{\mathcal{L}\{ x\}\left( s \right) }= \frac{\int^{\infty}_{0} z\left( t \right) e^{-st} dt}{\int^{\infty}_{0} x\left( t \right) e^{-st} dt }$$
And for the system B: $$ H_B(s)= \frac{Y\left( s \right) }{Z\left( s \right) } = \frac{\mathcal{L}\{y\} \left( s \right) }{\mathcal{L}\{ z\}\left( s \right) }= \frac{\int^{\infty}_{0} y\left( t \right) e^{-st} dt}{\int^{\infty}_{0} z\left( t \right) e^{-st} dt }$$
Applying the properties of Laplace transforms:
$$ \mathcal{L}\{ \frac{d^2 \, z(t)}{d \, t^2} + 6 \frac{d\, z(t)}{d\, t} + 8 z\left( t \right) \} = \mathcal{L} \{ \frac{d\, x(t)}{d\, t} + 2x\left( t \right) \} $$ $$ \Rightarrow s^2 \mathcal{L}\{ z\} +6s \mathcal{L}\{ z\} +8 \mathcal{L}\{ z\} = s\mathcal{L} \{ x\} +2\mathcal{L} \{ x\} $$ $$ \Rightarrow H_A(s)= \frac{\mathcal{L} \{ z(t) \}}{\mathcal{L} \{ x(t) \}} = \frac{s+2}{(s+2)(s+4)}=\frac{1}{s+4} $$ $$ \Rightarrow h_A=e^{-4t} $$
(in this last line, the original expression was wrong. It was fixed thanks to @KwinvanderVeen) for $s\neq -2$. We also have that:
$$ H_G(s)=\frac{Y(s)}{X(s)} = \frac{Y(s)}{Z(s)} \frac{Z(s)}{X(s)} = H_B H_A = \mathcal{L} \{ (h_B*h_A )(t) \} $$ $$ \Rightarrow \mathcal{L}\{ h_G\}=H_G(s)= \mathcal{L}\{ (h_B*h_A)(t) \} $$ $$ \Rightarrow h_G=h_B*h_A = \int_{0}^{t} h_B(\tau ) h_A(t-\tau )d\tau = e^{-4t}(t e^t-e^t+1) $$
(this last line was also fixed thanks to @KwinvanderVeen). And I think that last line would the the unit impulse response, and the answer to question 1.
Now, I tried to solve question 2 with the suggestions of the same commenter. If the input is periodic, then I think it follows that:
$$ x(t)= e^{1-t} \quad ; \quad 0<t<1 \quad ; \quad T=1 $$ $$ x(t)=e^{2-t} \quad ; \quad 1<t<2 \quad ; \quad T=1 $$
And in general, for $n \in \mathbb{N} $: $$ x(t)=e^{n-t} \quad ; \quad n-1<t<n \quad ; \quad T=1 $$
Then using the formula for the convolution integral: $$ y(t)= \left( h_G*x \right) (t) =e^{n-t} \int_{n-1}^{n} e^{-3\tau } (\tau e^{\tau} -e^{\tau} +1 ) d\tau $$
for $n-1<t<n $. Is that the answer? Can i leave the expression like that?